EXPERIENCE OF MINORITY SEXUAL GROUP IN MALAYSIA: THE RELATIONSHIP BETWEEN PERCEIVED DISCRIMINATION AND PSYCHOLOGICAL WELL-BEING - Mohd Firdaus Ninam Shah; Qarem Mohamed Mustafa (Journal of Islamic, Social, Economics and Development, 2022)
Even though same sex romantic relationship or homosexual relationship is notaccepted in Malaysia, the numbers of homosexual males are expected to increase based on theparticipation of an annual sexuality rights festival named â€œSeksualiti Merdekaâ€ which startedin 2008. There are several studies in Malaysia that describe the challenges faced by sexualminority groups namely being discriminated upon which also put their psychological wellbeingat risks. The current study aims to identify the relationship between sociodemographicvariables, perceived discrimination, and psychological well-being among homosexuals male inMalaysia. Based on purposive sampling, a total of 136 Malaysian gay men were purposivelyrecruited through social media outlets, as well as email by responding to a link created for theonline survey measuring perceived discrimination and presence of psychological distress.Pearson correlation analysis indicates a significant negative relationship between age andeducational background with psychological distress while a significant positive relationshipbetween perceived discrimination and psychological distress specifically symptoms ofsomatization, anxiety, and depression. Moreover, multiple regression suggests perceiveddiscrimination to significantly predict the presence of psychological distress. These highlightthe importance of exploring the experience of homosexuals male in Malaysia since thechallenges of each sexual minority group is unique.